2000
DOI: 10.1063/1.1331353
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and irreversible processes in donor-doped Pb(Zr,Ti)O3

Abstract: In this letter, the reversible and irreversible polarization contributions in donor-doped Pb(Zr,Ti)O3 are investigated using conventional capacitance–voltage (C–V) and hysteresis measurements. The dependence of the Rayleigh coefficient in the subcoercive regime on the doping concentration is investigated and shown to be consistent with the assumption of an interaction of the domain walls with randomly distributed defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…4,5 Such behavior may cause several effects on the dielectric behavior through interaction with domain walls. 6,7 Recently, it was found that in sintering of Y 2 O 3 -doped BTO with Y 2 O 3 higher than 0.80 mol %, presumably exceeded the solid solubility of Y 2 O 3 in BTO, is improved by both enhanced densification ͑by solid-solution defect͒ and suppressed coarsening ͑by second-phase pinning͒. 8 These results demonstrate the performance of our capacitors for future piezoelectric resonators consuming low energy levels at low phase transition temperature.…”
mentioning
confidence: 59%
“…4,5 Such behavior may cause several effects on the dielectric behavior through interaction with domain walls. 6,7 Recently, it was found that in sintering of Y 2 O 3 -doped BTO with Y 2 O 3 higher than 0.80 mol %, presumably exceeded the solid solubility of Y 2 O 3 in BTO, is improved by both enhanced densification ͑by solid-solution defect͒ and suppressed coarsening ͑by second-phase pinning͒. 8 These results demonstrate the performance of our capacitors for future piezoelectric resonators consuming low energy levels at low phase transition temperature.…”
mentioning
confidence: 59%
“…Between A and B the process is fully reversible, while between B and E irreversibility is involved. Bolten et al 16 pointed out that in the ferroelectric P-E loops, the reversible part can be described by a straight line without any hysteretic heat loss since the contribution mainly arises from the ionic and electronic polarization. This straight line should cross through the center of the hysteresis.…”
Section: Arxiv:160803401v3 [Cond-matmtrl-sci] 30 Aug 2016mentioning
confidence: 99%
“…The Rayleigh law has been widely observed in ferromagnetic materials [2], but also in ferroelectric ceramics [3,4]. The current theoretical interpretation of this law is based on a 1942 paper by Néel [5], who derived the law formulating the magnetization process as the dynamics of a point (i.e.…”
Section: Introductionmentioning
confidence: 99%